Planning, development pressure, and change in green infrastructure quantity and configuration in coastal Texas. (March 2022) - Woodruff, Sierra; Bae, Jinhyun; Sohn, Wonmin; Newman, Galen; Tran, Tho; Lee, Jessica; Wilkins, Chandler; Van Zandt, Shannon; Ndubisi, Forster
Abstract: Land-use change is a lead driver of ecological degradation in coastal regions. By guiding where development and open space are located, local land use plans are theorized to be an important tool to protect green infrastructure in coastal areas and their related services. Higher quality plans are expected to lead to greater protection of green infrastructure (GI). Using multiple linear regression, we test whether the presence and quality of comprehensive plans are related to change in GI landscape configuration between 2000 and 2016 in cities along Texas' coast. We find that comprehensive planning and plan quality are negatively associated with change in GI quantity and landscape pattern. Our results suggest that, in Texas, planning is mostly reactive; development pressure and environmental degradation likely lead to both loss of green infrastructure and city adoption of comprehensive plans. Highlights: Planning in coastal Texas may be a reaction to development pressure, rather than proactively preventing environmental loss. Flood risk is associated with higher protection of green infrastructure. Cities in coastal Texas with comprehensive plans experienced greater loss of green infrastructure than cities without plans. Similarly, cities with higher quality plans experienced greater loss and degradation of green infrastructure.